The outlook for the global supply of oil: Running on faith? - Olivier Gervais; Ilan Kolet (Bank of Canada, 2009)
The dramatic reduction in global demand, and the decline in the spot price of crude oil in the second half of last year, may have significant implications for the future supply of oil. Investments in conventional methods of extraction have been constrained, since easily accessible oil reserves are typically concentrated in countries with geopolitical uncertainty and/or state-run oil companies. Moreover, nearly half of all global oil production, and roughly 75 per cent of proven reserves, are accounted for by the Organization of the Petroleum Exporting Countries (OPEC). In this paper, the authors assess the implications of recent developments for the future supply of oil. They find that (i) the OPEC cuts announced in December 2008 could provide important support for prices in the coming year, and (ii) low prices have depressed, and may continue to depress, oil infrastructure investment, and thus could amplify existing supply constraints.
Keywords: Q41; Q43; 330; Business fluctuations and cycles; Inflation and prices; International topics; Erdölvorkommen; Mineralölmarkt; Ölpreis; Welt